The Necessity of Establishing a Unified Program of Activities for the Prevention of Violence Among Children in the Republic of Serbia - Stevanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
Forms of violence among children, with which the scientific, professional and general public in Serbia has recently been faced, show an increase in more serious forms of violence. Taking into account this fact, the author points out the need for appropriate action by all responsible parties and the necessity of making a unique program of activities for the prevention of violence among children. The paper also gives a brief review of certain preventive activities that have been implemented primarily in the school environment in the Republic of Serbia, as well as a review of some examples of good practice from around the world.